HUBUNGAN SANITASI LINGKUNGAN, MORBIDITAS DAN STATUS GIZI BALITA DI INDONESIA (RELATIONSHIP BETWEEN ENVIRONMENTAL SANITATION, MORBIDITY AND NUTRITIONAL STATUS OF UNDER-FIVE CHILDREN IN INDONESIA) - Tjetjep Syarif Hidayat; Noviati Fuada (Persagi, 2011)
ABSTRACT Background: A complex interplay of factors, such as household access to food, women’s status, caring practices, disease and access to safe water, sanitation and basic health services, affect a child’s nutrition. Objectives: To analyze the relationships between environmental sanitation, morbidity, and nutritional status of under-five children. Method: Data of the Basic Health Research (Riskesdas) 2007 was utilized for the analysis. Data samples is 43.162 children. Descriptive (chi-square) was conducted to examine the relationship between environtmental sanitation and nutritional status, the relationship between morbidity and nutritional status of children under five. Results: Sample of under-five children were 43.3 percent at age 37-59 months. Seventy-three percent of parents toddlers, are at the age of 26-45 years of age. Most parents (72.1%) had education below high-school. Based on anthropometric indicators of under-five children, 18.4 percent underweight, 36.8 percent stunting and 14.1 percent wasting. There is a significant association between the incidence of diarrheal diseases in children under five nutritional status indicators based on weight for age, height for age, and weight for height (BB/U, TB/U and BB/TB). Respiratory disease was significantly associated with indicators of nutritional status based on weight for age and height for age. There is a significant association between a healthy environmental sanitation with the nutritional status of under-five children by weight for age indicator. Conclusion: Nutritional status of under-five children most commonly associated with environmental sanitation and morbidity are indicators of nutritional status based on body weight for age. Keywords: children under five years, environmental sanitation, morbidity, nutritional status ABSTRAK Latar Belakang: Interaksi kompleks faktor-faktor, seperti akses keluarga terhadap makanan, status ibu, praktik pengasuhan, penyakit, serta akses terhadap air yang aman, sanitasi dan pelayanan kesehatan dasar, memengaruhi gizi anak. Tujuan: Menganalisis hubungan antara sanitasi lingkungan, morbiditas, dan status gizi anak di bawah usia lima tahun (balita). Metode: Data Riset Kesehatan Dasar (Riskesdas) 2007 digunakan untuk analisis. Sampel data sebesar 43.162 balita. Uji chi-square dilakukan untuk mengetahui hubungan antara sanitasi lingkungan dan status gizi, hubungan antara morbiditas dan status gizi anak balita. Hasil: 43,3 persen sampel anak balita berusia 37-59 bulan. Tujuh puluh tiga persen orang tua balita berusia 26-45 tahun. Sebagian besar orang tua (72,1%) berpendidikan di bawah SMA. Berdasarkan indikator antropometri, 18,4 persen anak balita mengalami gizi kurang, 36,8 persen pendek (stunting) dan 14,1 persen kurus. Ada hubungan signifikan antara kejadian penyakit diare pada anak di bawah lima tahun dengan status gizi berdasarkan indikator berat badan menurut umur, tinggi badan menurut umur, dan berat badan menurut tinggi badan (BB/U, TB/U dan BB/TB). Penyakit pernapasan secara bermakna berhubungan dengan indikator status gizi berdasarkan berat badan menurut umur dan tinggi badan menurut umur. Ada hubungan yang signifikan antara sanitasi lingkungan yang sehat dengan status gizi anak balita dengan berat badan menurut umur. Kesimpulan: Status gizi anak balita paling umum yang berhubungan dengan sanitasi lingkungan dan morbiditas adalah indikator status gizi berdasarkan berat badan menurut umur. [Penel Gizi Makan 2011, 34(2): 104-113] Kata kunci: anak balita, sanitasi lingkungan, morbiditas, status gizi